Diastereoselective Lithiation of N-Benzyl Pyrroloimidazolones Derived from l-Proline Hydantoin - Emberson, Kassandra; Tran, Ngan; Metallinos, Costa (Synlett, 2017)
An N-benzyl pyrroloimidazolone derived from l-proline hydantoin undergoes asymmetric lithiation with n-BuLi/TMEDA in toluene to give products of electrophile quench (E+) that range from 87:13 to 91:9 diastereomeric ratio (dr). All products appear to have the same relative stereochemistry as determined by transmetalation of benzylic stannanes, which gave identical major diastereomers for several products as to what was observed by direct lithiation–substitution of the starting material. X-Ray crystallography of the major diastereomer of the benzophenone adduct established (R)-configuration at the benzylic center, i.e., anti stereochemistry with respect to the imidazolone. Lithiation of a selectively deuterated analogue of the starting material according to the optimized conditions, followed by benzophenone quench, gave diastereomeric products with far lower selectivity (53:47 dr) than lithiation of the non-deuterated analogue (91:9 dr) owing to a large primary kinetic isotope effect. These preliminary results imply that metalation of the N-benzyl pyrroloimidazolone may follow an asymmetric deprotonation pathway to give a benzylic carbanion that retains its configuration during electrophile quench.
Keywords: diastereoselective; lithiation; benzylic; imidazolone; deuteration; transmetalation; chiral auxiliary